Non-persistence with anti-platelet therapy and long-term mortality after ischemic stroke: A nationwide study - Kim, Seung Jae; Kwon, Oh Deog; Choi, Ho Chun; Lee, Eung-Joon; Cho, BeLong (PloS one, 2021)
We tried to investigate the effect of non-persistence with antiplatelets after ischemic stroke on long-term all-cause mortality (ACM). We selected newly diagnosed ischemic stroke patients aged ≥20years who were newly treated with aspirin or clopidogrel from 2003-2010 Korean National Health Insurance Service-National Sample Cohort, a random sample of 2.2% of total population. Subjects were divided into two pairs of groups according to persistence with antiplatelets at 6 and 12 months: those who discontinued antiplatelets within 6 months (DA6M) and those who continued them for 6 or months or more (CA6M); and those who discontinued antiplatelets within 12 months (DA12M) and those who continued them for 12 months or more (CA12M). Those who died within 6 months among DA6M and those who died within 12 months among DA12M were excluded along with those with medication possession ratio<80% among CA6M and CA12M. Subjects were followed-up until death or December 31, 2013. Among 3,559 total subjects, DA6M were 1,080 and CA6M were 2,479 while, out of 3,628 total patients, DA12M were 1,434 and CA12M were 2,194. The risks of ACM [adjusted hazard ratio (aHR), 2.25; 95% confidence interval (CI), 1.94-2.61], cerebro-cardiovascular disease (CVD) death (aHR, 2.52; 95% CI, 1.96-3.24) and non-CVD death (aHR, 2.11; 95% CI, 1.76-2.64) of DA6M were all significantly increased compared to CA6M. DA12M also had significantly higher risks of ACM (aHR, 1.93; 95% CI, 1.65-2.25), CVD mortality (aHR, 2.13; 95% CI; 1.63-2.77) and non-CVD mortality (aHR, 1.83;95% CI 1.51-2.22) than DA12M but aHRs were lower than that between DA6M and CA6M. The difference rates of ACM, CVD death, and non-CVD death between non-persistent and persistent groups all continuously widened over time but the degree of difference was gradually decreased. Maintaining antiplatelets for the first 12 months after ischemic stroke reduces long-term risks of both CVD death and non-CVD death.